Association between the level of municipality healthcare services and outcome among acutely older patients in the emergency department: a Danish population-based cohort study. Issue 4 (24th April 2019) - Tanderup, Anette; Ryg, Jesper; Rosholm, Jens-Ulrik; Lassen, Annmarie Touborg
Abstract : Objectives: This study aims to describe the association between use of municipality healthcare services before an emergency department (ED) contact and mortality, hospital reattendance and institutionalisation. Design: Population-based prospective cohort study. Setting: ED of a large university hospital. Participants: All medical patients ≥65 years of age from a single municipality with a first attendance to the ED during a 1-year period (November 2013 to November 2014). Primary and secondary outcome measures: Patients were categorised as independent of home care, dependent of home care or in residential care depending on municipality healthcare before ED contact. Patients were followed 360 days after discharge. Outcomes were postdischarge mortality, hospital reattendance and institutionalisation. Results: A total of 3775 patients were included (55% women), aged (median (IQR) 78 years (71–85)). At baseline, 48.9% were independent, 34.9% received home care and 16.2% were in residential care. Receiving home care or being in residential care was a strong predictor of mortality, hospital reattendance and institutionalisation. Among patients who were independent, 64.3% continued being independent up to 360 days after discharge. Even among patients ≥85 years, 35.4% lived independently in their own house 1 year after ED contact. Conclusion: Prehospital information on municipality healthcare is closely related to patient outcome in older ED patients. It might have the potential to be used in risk stratification and planning of needs of older acute medical patients attending the ED.